NFORMATION AND COMMUNICATION TECHNOLOGIES AND THEIR RELATIONSHIP WITH THE QUALITY OF THE SERVICES AT THE HOTEL "SOL DEL ORIENTE" DE THE PROVINCE OF CORONEL PORTILLO, UCAYALI, 2014 - León Mendoza, Omar Viviano (2019)
In the present work, the main objective was to establish the degree of association between the variables information and communication technologies and the quality of the services of the hotel sol del Oriente. Being considered as hypothesis of the investigation, the existence of a direct and significant relationship between information and communication technologies and the quality of the services of the Hotel "Sol del Oriente" of Ucayali, 2014; to fulfill this purpose, a correlational work was executed, through an ex post facto-descriptive or simple-correlational design. The survey technique was used in the study, and survey questionnaires were used as instruments for data collection. The results obtained were processed with the statistical program SPSS Version. 22. Achieving the product of the study, through the testing of the general hypothesis, using the Pearson correlation coefficient, with a level of significance of 5% and a "r" of Pearson equal to 0.524, establishing the existence of a direct and significant positive association media between Information and Communication Technologies and the quality of the services of the hotel "Sol del Oriente", Ucayali, 2014. KEYWORDS: Information and Communication Technologies and the Quality of Services.